An atomic switch using oxygenated amorphous carbon as solid electrolyte. (12th December 2018) - Xu, Han; Wang, Qi; Ma, Yaodong; Dang, Honggang; Guo, Pengqian; Yang, Huan; He, Deyan
Abstract: Atomic switches based on carbon films as electrolyte have received great attention due to the many advantages of carbon, but their low high-resistance state and poor thermal stability of the device have greatly limited their further development. Here, we have constructed an atomic switch in which we use an oxygenated amorphous carbon (a-CO x ) film as a solid electrolyte through introducing O2 gas during the sputtering of a graphite target. The reversible and steady resistive switching effect with a resistance ratio over two orders of magnitude was achieved. While the sputtered pure C film has a low resistivity, which is not suitable for an atomic switch, the resistance of a-CO x increases substantially with the partial pressure of O2 . More importantly, we found that the higher the partial pressure of O2, the better the high temperature retention. In combination with the two-step reset process in which the heat and electric fields respectively act and mutable forming voltage with temperature, the achieved high temperature retention for more oxidized carbon films is most likely due to the more reduction of structural defects caused by the greater addition of oxygen during the deposition process and the chemical inertness of a-CO x .